Sweats of treats bakery and cakes - Omar, Muhammad Afiq Akmal; Ali, Nur Syazwani; Zamri, Nurlydiana; Kamal, Zulaika (2021)
Sweets of Treats is a partnership-based company of four employees, including the General Manager and Operational Manager, the Manager of Administration, the Marketing Manager and the Financial Manager. The total capital for the business to start is RM289,430 which RM198,008 of it is the loan that we made from SME Bank. Sweets of Treats provide a various type of breads and cakes and our signature cake is the Korean’s cake where customer can custom their own design of the cake. So, everybody can enjoy our cake, especially children because they love their favourite cartoon character to be as their cake. Our company is located at Kuala Lumpur with the address: 5, Jalan Anggerik Aranda BG 31/BG, Kota Kemuning, 40460 Shah Alam, Selangor. Sweats of Treats is a business dedicated to the development of food. Bread and cakes are the food that people could find if they don't feel like consuming rice. The variations in size and form make the cake look appealing and perfect for almost any function. This cake gives a convenient and fresh quality to be such a valuable product, as people absolutely will enjoy food with good quality. In addition, our company has many advantages through simple ways and ingredients and we are positive that our business in Malaysia will be able to grow and expand efficiently. In order to make it even more appealing but also unique, we have agreed to create some development by using our imagination and the unique concept of making bread and cakes. Today, colour is one of the main elements in any product to make colourful cakes with flavour and multiple variations of bread. Usually, people who work during normal working hours and students do not have much breakfast time. So, because of our fresh product, consumers can always grab a packet of bread with various fillings then go to work. Simple and fast, just like that. Our production of bread and cakes is expected to be a profitable venture if everything is performed following the new trends and conducted on a large scale. We believe that our company will expand in the near future because the latest idea for our bread and cakes will not only boost demand, but the bread also can be a new regular snack. This brings us even more benefits in terms of making our product increasingly successful and sustainable over the long term.